Exciton line broadening in CdxZn1?xTe/ZnTe multiple quantum wells - HEGARTY, JOHN (American Institute of Physics, 1988)
We have investigated Cdx Zn1?xTe/ZnTe multiple quantum wells using absorption techniques. We have observed sharp excitonic features at low temperatures which strongly broaden at room temperature. The strength of the exciton-phonon coupling is determined from linewidth analysis. The large measured coupling explains the lack of well defined exciton resonances at room temperature, an important consequence for their use as optoelectronic devices.
PUBLISHED
Keywords: EXCITONS; VISIBLE SPECTRA; ABSORPTION SPECTRA; PHONON?EXCITON INTERACTIONS